REVIEWING ADVANCEMENT IN TELECOMMUNICATIONS INFRASTRUCTURE: A COMPARATIVE STUDY OF AFRICA AND THE USA - Chinedu Alex Ezeigweneme; Aniekan Akpan Umoh; Valentine Ikenna Ilojianya; Abimbola Oluwatoyin Adegbite (Acta Informatica Malaysia)
This study presents a comparative analysis of recent advancements in telecommunications infrastructure in Africa and the United States, shedding light on the dynamic landscape of connectivity in these regions. The research explores the technological strides made in both continents and evaluates their respective impacts on fostering communication, economic growth, and social development. In Africa, the telecommunications sector has undergone significant transformations, with a surge in mobile connectivity playing a pivotal role. The study investigates the deployment of 4G and emerging 5G technologies, the expansion of fiber-optic networks, and the proliferation of mobile devices. Additionally, it examines how these advancements contribute to bridging the digital divide and empowering underserved communities. Conversely, the United States has witnessed continuous innovation and investment in its well-established telecommunications infrastructure. The analysis delves into the rollout of 5G networks, the evolution of broadband technologies, and the integration of Internet of Things (IoT) devices. The study also explores the role of public-private partnerships and regulatory frameworks in shaping the telecommunications landscape. By comparing these advancements, this research aims to identify key trends and best practices that have contributed to enhanced connectivity in both regions. Moreover, it investigates the socio-economic implications of improved telecommunications infrastructure, such as increased access to education, healthcare, and business opportunities. The findings of this study contribute to the global understanding of the diverse approaches to telecommunications infrastructure development and highlight areas where collaboration and knowledge exchange between Africa and the USA can further accelerate progress. As the world becomes increasingly interconnected, the lessons learned from these regions can inform strategies for addressing connectivity challenges and fostering inclusive technological development on a global scale.